Integral and humanistic education: Developing the creative capacities of the human being - Mejia, Elias Mejia; Flores, Francis Díaz; Retamozo-Zegarra, María; Damian-Nuñez, Edgar; Campana-Concha, Abelardo (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between humanism and education, emphasizing the development of fundamental human capacities such as thought, language, psychomotricity, and sociability, which serve as the foundation of culture and human potential. A comprehensive literature review and documentary analysis were conducted, drawing from the work of leading scholars and futurists to identify how education shapes human capacities in a rapidly changing world. The analysis reveals that advances in science and technology have transformed educational paradigms by introducing innovative teaching methods, expanding global interactions, and fostering collaborative learning. Furthermore, intensified cognitive activity among individuals has accelerated scientific and technological progress, producing remarkable achievements in human history. Education emerges as a crucial mediator that bridges individual potential with societal development. Humanism in the 21st century highlights the centrality of education in cultivating human capacities, promoting cultural evolution, and preparing individuals to adapt and contribute meaningfully to global challenges. These insights underscore the need for educational systems to adopt humanistic approaches that not only integrate technological advances but also prioritize the holistic development of learners to ensure sustainable cultural and social progress.